2013
DOI: 10.5194/hess-17-961-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change and anthropogenic activities on stream flow and sediment discharge in the Wei River basin, China

Abstract: Abstract. Reduced stream flow and increased sediment discharge are a major concern in the Yellow River basin of China, which supplies water for agriculture, industry and the growing populations located along the river. Similar concerns exist in the Wei River basin, which is the largest tributary of the Yellow River basin and comprises the highly eroded Loess Plateau. Better understanding of the drivers of stream flow and sediment discharge dynamics in the Wei River basin is needed for development of effective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 20 publications
5
101
2
1
Order By: Relevance
“…During the last 50 years, the runoff in Weihe River has dramatically decreased; principally in the late 1990s when the average was only 3.60 billion m³ compared to 6.20 billion m³ in the 1950s [22,23]. The mean annual sediment contribution of the Weihe River to the Yellow River is 390 billion kg, and in the flood season occurring between June-September it reaches approximately 90% of the mean annual sediment yield [4]. The average sediment yield in the 2000's was reduced to 160 billion kg, principally due to human activity and climate change, compared to 680 billion kg in the 1950's [24].…”
Section: Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…During the last 50 years, the runoff in Weihe River has dramatically decreased; principally in the late 1990s when the average was only 3.60 billion m³ compared to 6.20 billion m³ in the 1950s [22,23]. The mean annual sediment contribution of the Weihe River to the Yellow River is 390 billion kg, and in the flood season occurring between June-September it reaches approximately 90% of the mean annual sediment yield [4]. The average sediment yield in the 2000's was reduced to 160 billion kg, principally due to human activity and climate change, compared to 680 billion kg in the 1950's [24].…”
Section: Study Areamentioning
confidence: 99%
“…The data reveal a 300% decline in runoff and sediment yield from soil and water conservation programs from the 1970's to the 1990's relative to the 1960's. Water projects, such as reservoirs and dams, disturb the runoff by increasing the evaporation, the drinking water supply and the agricultural irrigation while Prior research has been conducted to explain the causes of decreasing runoff and sediment yield in the WRB [4,22,32]. These studies concluded that climate change, especially the variations in precipitation and anthropogenic activity, were the main culprits.…”
Section: Variations In Annual Runoff and Sedimentmentioning
confidence: 99%
See 3 more Smart Citations